THE ANALYSIS OF WORLD TENDENCIES AND PROSPECTS OF DEVELOPMENT OF PASSENGER CAR BUILDING - Fediushyn, Yu. M.; Loboiko, L. M.; Donchenko, A. V.; Pshinko, O. M.; Prykhodko, V. I.; Shkabrov, O. A. (Science and Transport Progress, 2005)
In article world (global) tendencies of development of designs of carriages and prospect of their development are analyzed.